2021
DOI: 10.1016/j.patol.2020.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Multi-organ pathological findings associated with COVID-19 in postmortem needle core biopsies in four patients and a review of the current literature

Abstract: Hallazgos patológicos multi-orgánicos asociados a COVID-19 a través de biopsias con aguja gruesa postmortem y revisión de la literatura actual. La enfermedad de coronavirus 2019 (COVID-19) ha afectado de forma mundial causando intensa morbimortalidad. Los hallazgos patológicos son claves para entender su patogénesis. A través de biopsias con aguja gruesa postmortem, intentamos responder a las incógnitas que giran en torno a la severidad de ésta infección. Se enviaron muestras de cuatro pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
2
1
Order By: Relevance
“…Binuclear and multinuclear hepatocytes were identified, similar to the findings of Wang et al [33], who report that this morphological phenomenon may be attributed to reactive changes. Few hepatocytes showed glycogenic intranuclear vacuolisation, a finding that contrasts with that found by Pessolani et al [34], who described many hepatocytes with this finding. In a series of 40 cases, Lagana et al [35] found macrovesicular steatosis in all patients, whereas microvesicular steatosis was found in our patient.…”
Section: Discussioncontrasting
confidence: 90%
“…Binuclear and multinuclear hepatocytes were identified, similar to the findings of Wang et al [33], who report that this morphological phenomenon may be attributed to reactive changes. Few hepatocytes showed glycogenic intranuclear vacuolisation, a finding that contrasts with that found by Pessolani et al [34], who described many hepatocytes with this finding. In a series of 40 cases, Lagana et al [35] found macrovesicular steatosis in all patients, whereas microvesicular steatosis was found in our patient.…”
Section: Discussioncontrasting
confidence: 90%
“…Clinical trials of surfactant use in ARDS in SARS-CoV-2 infections are currently underway. Despite important differences in the underlying populations and the methods utilized, this MITS-based study of decedents presenting with symptoms of respiratory disease shows substantial conformity with prior results from other parts of the world concerning lung pathology among persons testing positive for SARS-CoV-2 infection [23,34].…”
Section: Plos Onesupporting
confidence: 67%
“…Recently, studies of larger numbers of decedents and meta-analyses of smaller studies have been published [ 18 , 19 ]. Because ARDS is common in severely ill patients with SARS-CoV-2 infections, the large majority of the literature has focused on the analysis of lung tissue samples [ 20 , 21 ], with only a few study reporting on multiple tissue findings [ 19 , 22 , 23 ]. This study documents post-mortem lung, liver and heart histopathology, and blood and lung culture and molecular assay findings among adult decedents in Soweto, South Africa diagnosed with respiratory symptoms, and compares these findings based on SARS-CoV-2 infection status diagnosed either ante-mortem or post-mortem.…”
Section: Introductionmentioning
confidence: 99%
“…The spleen typically shows lymphocytic depletion of the white pulp, leading to a decrease or absence of lymphoid follicles. Kidney involvement manifests as acute tubular necrosis (ATN), characterized by glomerular capillary thrombi, vacuolization, and dilatation of tubules 6 .…”
Section: Intruductionmentioning
confidence: 99%